Processing Method of Soil Temperature Time Series and Its Application in Geothermal Heat Flow - Yang, Liming; Song, Rongcai; Dong, Ben; Yin, Likun; Fan, Yifan; Zhang, Bo; Wang, Ziwei; Wang, Yingchun; Dong, Shuyi (Frontiers in Earth Science, 2022)
Nowadays, geothermal resources have become one of the important means for mankind to solve global energy problems and environmental problems, and the exploration and development of geothermal resources are of great significance for sustainable development. However, in view of the complex geological background of the plateau region, the number of heat flow measurement points in this area is small or even blank, thus becoming an important factor limiting the exploration of geothermal resources in this region. In this paper, a new model based on Fourier analysis and heat conduction principle is established to process and analyze the long-term monitoring data of soil temperature and eliminate the influence of temperature change on soil temperature as far as possible, so as to improve the calculation accuracy of soil conduction heat dissipation. The experimental results show that the fluctuation range of soil temperature at 20 cm before correction was large, and the fluctuation range was 2.58℃-14.284℃, which was because the soil here was closer to the land surface and was affected too much by the temperature fluctuation, and as the soil depth deepened, the temperature fluctuation slowly became smaller, and the fluctuation range was 6.67℃-11.15℃ at 50 cm out, but the effect of temperature fluctuation was still obvious. And the fluctuation range was basically reduced to within 0.3℃ after temperature correction. In this method, the thermal diffusion coefficients of the soil at different depths can be obtained, and the calculated temperatures at the corresponding depths can also be obtained, which can be used to infer the approximate ground temperature gradient of the measured area. This study aims to develop a convenient and fast model for processing soil temperature time series and to provide technical support for developing geothermal resources in highland areas or assessing the geothermal potential of the region.